Stercoral Perforation of the Rectum:: A Case Report and Review of Literature - Mohammad M. Abbas; Aisha M. Abdulrahman; Nouf Y. Akeel; Majid M. Manouri (Journal of King Abdulaziz University: Medical Sciences, 2023)
Stercoral perforation of the rectum is a rare disease. It is a potentially fatal complication of untreated chronic constipation. Presenting symptoms and signs are variable according to the site of the perforation. A 60-year-old male patient presented to the emergency room with dizziness and decreased level of consciousness. He was admitted for management under care of medical team as a case of urosepsis. Two days after admission he developed picture of Fournier gangrene. The underlying cause was found to be rectal perforation. Stercoral perforation is an emergency that can be missed if not highly suspected. We present a case of stercoral rectal perforation with picture of urosepsis and Fournier gangrene as presenting symptoms. Stercoral perforation is a potentially fatal disease with unspecific presentations that need to be highly suspected in patients with chronic constipation and severe sepsis.